2012
DOI: 10.1038/mtna.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

AON-mediated Exon Skipping Restores Ciliation in Fibroblasts Harboring the Common Leber Congenital Amaurosis CEP290 Mutation

Abstract: Leber congenital amaurosis (LCA) is a severe hereditary retinal dystrophy responsible for congenital or early-onset blindness. The most common disease-causing mutation (>10%) is located deep in intron 26 of the CEP290 gene (c.2991+1655A>G). It creates a strong splice donor site that leads to insertion of a cryptic exon encoding a premature stop codon. In the present study, we show that the use of antisense oligonucleotides (AONs) allow an efficient skipping of the mutant cryptic exon and the restoration of cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 29 publications
1
106
1
Order By: Relevance
“…An ideal candidate for AON-based therapy is a recurrent intronic mutation in CEP290 (c.2991 + 1655A > G) that is causative for up to 15 % of all LCA cases in the US and several European countries (den Hollander et al 2006;Perrault et al 2007;Stone 2007;Coppieters et al 2010). This mutation activates a cryptic splice donor site that results in the insertion of a pseudo-exon with a premature termination codon to approximately 50-75 % of the CEP290 transcripts (den Hollander et al 2006;Gerard et al 2012). We have shown that, in lymphoblastoid and fibroblast cells from LCA patients with a homozygous intronic CEP290 mutation, administration of AONs targeting the pseudo-exon fully restores normal CEP290 pre-mRNA splicing (Collin et al 2012;Gerard et al 2012) (Fig.…”
Section: Aon-based Therapy For Inherited Retinal Degenerationsmentioning
confidence: 99%
“…An ideal candidate for AON-based therapy is a recurrent intronic mutation in CEP290 (c.2991 + 1655A > G) that is causative for up to 15 % of all LCA cases in the US and several European countries (den Hollander et al 2006;Perrault et al 2007;Stone 2007;Coppieters et al 2010). This mutation activates a cryptic splice donor site that results in the insertion of a pseudo-exon with a premature termination codon to approximately 50-75 % of the CEP290 transcripts (den Hollander et al 2006;Gerard et al 2012). We have shown that, in lymphoblastoid and fibroblast cells from LCA patients with a homozygous intronic CEP290 mutation, administration of AONs targeting the pseudo-exon fully restores normal CEP290 pre-mRNA splicing (Collin et al 2012;Gerard et al 2012) (Fig.…”
Section: Aon-based Therapy For Inherited Retinal Degenerationsmentioning
confidence: 99%
“…Our previous study has demonstrated that the pH responsive peptides are capable of mediating both highly efficient DNA or siRNA transfection in mammalian cell lines [15] (Abbate et al, unpublished). Others have shown that LAH4 peptides can effectively deliver nucleic acids to patient derived primary fibroblasts [18] and facilitate intracellular delivery in vivo by way of subcutaneous injection of protein-based vaccines adjuvanted with Toll-like receptor 9 agonist CpG oligonucleotide (CpG) to generate enhanced CD8+ T cell immune responses and antitumor effects [19]. With proven efficacy in delivery to a variety of cultured, primary cells and tumour cells together with the first example of in vivo tolerance and efficacy, we were interested to develop a pH responsive peptide-based formulation that is suitable for effective nucleic acid delivery by pulmonary administration.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, AON-mediated correction of the c.2991 + 1665A > G CEP290 mutation in patientderived fibroblasts was demonstrated in two independent studies (19,20). The corrected gene exhibited improved transcription of the wild type transcript and restoration of cilia formation in the patient fibroblasts.…”
Section: Cep290mentioning
confidence: 96%